KONSEP DIRI PECINTA JAPANSE POP CULTURE DI KOTA PEKANBARU (STUDI KASUS PADA KOMUNITAS SEIKATSU COSPLAY) - Afril Wahyudi; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Cosplay or Cosplayer is an activity of dressing and behaving like a character in Japanese Animation or called Anime, this phenomenom originating from Japan is widespread through the use of social media and gets a lot of attention for social media users around the world. Reseached one the famous Cosplay Communities in Pekanbaru namely Seikatsu.The purpose of this study was to find out how the Cosplayers’ self-concept and how the environmental factors formed the selfconcept in this study, the subyek taking technique used purposive sampling which had determined the criteria in this study.The theory usedin the reasech is The Looking Glass Self of Charles Horton Cooley. The results of the study are the factors that cause the formation of a Cosplayer’s Self-concept is a friend, startingfrom a friend who introduces him to Japanese popular culture, so that Cosplayers who don’t know anything about Japanese Popular Culture began yo have an intrest in the culture originating form Japan. The Second is that the invironment introduces many new cultures such as Cosplay. Cosplay is often shown during big holidays such as New Year, Hallowen, Chinese New Year,even on Independence Day 17 August, not infrequently Mall and Hotel also make special event such as Japanse Cultural performance or called Bunkasai so that it attracts people’s attention, from the event the audience enjopys and likes what they see. And the third is the media, media plays a major role in the development of popular culture throughout the world. Cosplay which is Japanese popular culture is one the many fans of Japanese Animation or called Anime Keywords: Cosplay, Popular Japanese Culture, Self-concept.